The effectiveness of a modified Gui Zhi Fu Ling Wan formulation (Gynoclear™) for the treatment of endometriosis: a study protocol for a placebo-controlled, double-blind, randomised controlled trial - Armour, Mike (Trials, 2021)
BACKGROUND: Endometriosis is the presence of tissue similar to that of the endometrium outside the uterine cavity and is the most common cause of chronic pelvic pain. Current non-surgical treatments such as non-steroidal anti-inflammatories, oral contraceptive pills and hormonal treatments have limited effectiveness, and the side effect profile is bothersome. This study will evaluate the efficacy of Gynoclear™ by change in endometriosis-related pain based on the Endometriosis Pain Daily Diary (EPPD) scores. METHODS: This randomised, double-blind, placebo-controlled trial will recruit a minimum of 90 adult participants across Australia who have a laparoscopic visualisation/confirmation of endometriosis in the last 5 years and have current moderate or greater pelvic pain. Participants will be randomly allocated in a 1:1 ratio to receive either Gynoclear™ (active) or placebo. Gyncolear’s active ingredients are Carthamus tinctorius (Safflower), Cinnamomum cassia (Chinese cinnamon), Poria cocos (Hoelen), Paeonia suffriticosa (Tree peony), Paeonia lactiflora (Peony) and Salvia miltiorrhiza (Red sage). Participants are asked to complete a total of 5 months’ worth of pain diary entries via the EPDD v3, including 1-month screening, 2-month treatment period and 1-month post-treatment follow-up. The primary outcome variable is change in endometriosis-related pain based on the EPDD v3 scores. Secondary outcomes include change in health-related quality of life via the Endometriosis Health Profile (EHP-30), SF-12 and EQ-5D scores as well as changes in rescue analgesic usage, dyspareunia and fatigue via the EPDD. DISCUSSION: This study will determine the safety and efficacy of Gynoclear™ to reduce the severity and duration of non-cyclical pelvic pain, dysmenorrhoea, dyspareunia and other symptoms of endometriosis. Study outcomes will be of interest to health professionals and members of the public who suffer from endometriosis. TRIAL REGISTRATION: Australia and New Zealand Clinical Trials Registry ACTRN12619000807156. Registered on 3 June 2019. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13063-021-05265-x.